PENGEMBANGAN BAHAN AJAR DIGITAL MENGGUNAKAN BOOK CREATOR PADA MATERI LINGKUNGAN JADI RUSAK FASE C AWAL SEKOLAH DASAR: Penelitian Research and Development pada Peserta Didik Fase C Awal Sekolah Dasar Negeri Gang Aut Kota Bogor Semester Genap Tahun Ajaran 2023/2024 - Annastasya Maulida; R. Teti Rostikawati; Yudhie Suchyadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Development of Digital Teaching Materials Using Book Creator on Damaged Environmental Materials Phase C Early Elementary School. This research uses an R&D (Research and Development) approach at Gang Aut State Elementary School. The research subjects were students in class V-A at Gang Aut State Elementary School, consisting of 27 students. The research was conducted in the even semester of the 2023/2024 academic year. The aim of this research is to develop digital teaching materials using Book Creator on damaged environmental materials and determine their feasibility. This research uses the ADDIE (Analyze, Design, Development, Implementation and Evaluation) method. This research uses validation tests on experts, namely media experts, language experts and material experts. To develop and perfect digital book creator teaching materials, student and teacher responses are needed. The results of the validation test by media experts obtained a percentage of 94.3% with very appropriate criteria, language experts obtained a percentage of 100% with very appropriate criteria, material experts obtained a percentage of 91.43% with very appropriate criteria. The results of the student response questionnaire obtained a percentage of 80.67% with very feasible criteria, and the results of the teacher response questionnaire showed a percentage of 82% with very feasible criteria. Thus, it can be concluded that digital teaching materials using book creators are suitable for students to use in learning activities in elementary schools.